Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis PBL untuk Meningkatkan Hasil Belajar Fisika - Kholida Ismatulloh; Yosi Nur Kholisho; Bq. Malika Hr; Baiq Desi Dwi Arianti (Universitas Hamzanwadi, 2024)
This research aims to determine the effectiveness and response of students to the Student Worksheet (LKPD) that was developed. The type of research is research and development with a